2020
DOI: 10.30574/wjarr.2020.6.2.0115
|View full text |Cite
|
Sign up to set email alerts
|

Lung contusion mimicking COVID-19 pneumonia: A case report

Abstract: In December 2019, a series of pneumonia cases of unknown origin were determined in Wuhan, China. The disease, then, was named as 2019 novel coronavirus (2019-nCoV) and subsequently as COVID-19 officially by the World Health Organization (WHO). Its characteristics such as high infectivity and mortality makes COVID-19 a serious public health problem. It causes consumption of sources in healthcare facilities dealing with the disease. In this case report, we present you a patient admitted to our Emergency Departme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Six of these surveys were case reports that exclusively showed some similarities, although they did not conduct proper criteria to differentiate these two entities. 19 , 20 , 21 , 22 , 23 , 24 Five out of six case reports had pulmonary contusions, and their CT images showed bilateral multifocal lesions. Based on our results, we concluded that the prevalence of bilateral lung involvement is higher in pure pulmonary contusion, although it was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Six of these surveys were case reports that exclusively showed some similarities, although they did not conduct proper criteria to differentiate these two entities. 19 , 20 , 21 , 22 , 23 , 24 Five out of six case reports had pulmonary contusions, and their CT images showed bilateral multifocal lesions. Based on our results, we concluded that the prevalence of bilateral lung involvement is higher in pure pulmonary contusion, although it was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%